Subgingival plaque microbiota in HIV positive patients - J. A. Aas (Blackwell Synergy, 2007)
Aim: To describe and compare the predominant bacterial and fungal species associated with gingivitis, periodontitis, and linear gingival erythema (LGE), in HIV positive subjects with different immune status. Methods: Viral loads and CD4 levels determined HIV disease status. From pooled subgingival plaque, 16S and 18S rDNA were cloned and sequenced to determine species identity. Results: One hundred and nine bacterial species were identified from 14 subjects. Nearly half of the species were not cultivable. Notably, the classical putative periodontal pathogens, Treponema denticola, Porphyromonas gingivalis and Tannerella forsythia were below the limit of detection and were not detected. Species of Gemella, Dialister, Streptococcus and Veillonella were predominant. In one HIV positive subject with periodontitis and low viral load, Gemella morbillorum, a known opportunistic pathogen, constituted 84% of the clones. Saccharomyces cerevisiae was the only fungal species detected in an LGE subject and in periodontitis subjects with high viral loads. In periodontitis patients with low viral loads, Candida albicans was predominant, while S. cerevisiae was only a minor component. Conclusion: These case studies suggest that other bacterial species, rather than the classical periodontal pathogens, may be involved in periodontal diseases of subjects with HIV. These data are indicative of opportunistic infections in a highly susceptible immunocompromised host.